Miller’s Pyramid as a Predictor of Undergraduate Students’ Practical Competence in Preventing Chemical Laboratory Accidents - I Ketut Lasia; Ni Made Wiratini; I Ketut Budiada; I Gusti Ayu Nyoman Sri Wahyuni (Jurnal Inovasi Pendidikan Kimia, 2025)
Preventing accidents in chemistry laboratories is a critical concern, as laboratory activities involve chemical hazards, equipment risks, and procedural errors. One of the main contributing factors to laboratory accidents is inadequate student competence during practical activities. However, systematic predictors for assessing practicum competence are still rarely implemented. This study aims to examine the effectiveness of Miller’s Pyramid as a predictor of students’ practicum competence in preventing work-related accidents in chemistry laboratories. The research employed a descriptive evaluative design. The participants consisted of students from the Chemistry Department who were involved in laboratory practicums. The object of the study was students’ practicum competence based on the four levels of Miller’s Pyramid: knows, knows how, shows, and does. Data were collected through written tests, interviews, and direct observations using structured assessment rubrics. The collected data were analyzed descriptively and presented in percentage form. Student competence was categorized as good when at least 70% of the indicators at each Miller’s Pyramid level were achieved. The results showed that students’ competence at all levels of Miller’s Pyramid met the established criteria, indicating good overall practicum competence. Furthermore, the findings demonstrate that Miller’s Pyramid can effectively function as a predictor of students’ practicum competence related to laboratory safety. In conclusion, the application of Miller’s Pyramid provides a comprehensive framework for assessing and improving student competence, thereby contributing to the prevention of work accidents in chemistry laboratories